Focus on Earth Science. - Bishop, Margaret, Phyllis G. Lewis; Berry Sutherla (Columbus, Ohio A Bell and Howell Company, 1976)
It is a study of planet Earth its features, its firces, its place in the solar system, and its place in the universe. Basic principles of chemistry and physics are introduced to form the framework for understanding the changes that occur in stars, in planets, and in the earth`s matter.
Keywords: Science